Southeast Maluku District waters has abundance fisheries resources, especially small pelagic fisheries, but its poorly managed. That is identified from inadequate infrastructure with traditional fishing effort. Furthermore, the quality of human resources (fishermen) is still relatively low, characterized by weak management and skills so that adopting technology is time-consuming. The objectives of this study were to analyze the alternative policies and steps or actions priorities on the small - Jacomina Tahapary; Domu Simbolon; Tri Wiji Nurani (Forum Pasca Sarjana, 2010)
Southeast Maluku District waters has abundance fisheries resources, especially small pelagic fisheries, but its poorly managed.  That is identified from inadequate infrastructure with traditional fishing effort.  Furthermore, the quality of human resources (fishermen) is still relatively low, characterized by weak management and skills so that adopting technology is time-consuming.  The objectives of this study were to analyze the alternative policies and steps or actions priorities on the small pelagic fisheries development in Southeast Maluku District waters.  One of the approaches can be used for solving the development of small pelagic fisheries problems is analytical hierarchy process (AHP) method.  Study result showed alternative development priority on increasing the number of catches (0.316), improving the quality of human resources (0.309), sustainable development of fishing gear (0.225), and improvement of infrastructure facilities and fishing (0.150) in consitency ratio of 0.04. Appropriate policy measures in the form of short-term program is the improvement of fishing technology (0.237), motorization of fishing units (0.189), the economic empowerment of fishing communities (0.187), entered into a building where fish autions (0.137), conduct training and coaching (0.130) and strengthening institutional institutional management and operations (0.120) in consistency ratio of 0,05.  Conclusion is alternative development policy priority on increasing the amount of catch with the important aspects to be considered that biological aspects improving the efficiency of fishing gear, the economic aspect in improving labor income, the marketing aspect in strengthening the domestic market, the technical aspect of overcoming the influence of the physical environment of the selectivity tools and social aspects in improving the wages received by fishermen.  Actions taken to increase the catch is with the development of fishing technology.  Such measures are also useful for improving the quality of human resources (fishermen) in order to exploit fish resources responsibly and sustainably.   Key words: analitycal hierarchy process (AHP), small pelagic, Southeast Maluku District, strategy development